Advanced Microwave Imaging - Ahmed, Sherif Sayed; Schießl, Andreas; Gumbmann, Frank; Tiebout, Marc; Methfessel, Sebastian Dirk; Schmidt, Lorenz-Peter (IEEE Microwave Magazine, 2012)
Due to the enormous advances made in semiconductor technology over the last few years, high integration densities with moderate costs are achievable even in the millimeter-wave (mm-wave) range and beyond, which encourage the development of imaging systems with a high number of channels. The mm-wave range lies between 30 and 300 GHz, with corresponding wavelengths between 10 and 1 mm. While imaging objects with signals of a few millimeters in wavelength, many optically opaque objects appear transparent, making mm-wave imaging attractive for a wide variety of commercial and scientific applications like nondestructive testing (NDT), material characterization, security scanning, and medical screening. The spatial resolution in lateral and range directions as well as the image dynamic range offered by an imaging system are considered the main measures of performance. With the availability of more channels combined with the powerful digital signal processing (DSP) capabilities of modern computers, the performance of mm-wave imaging systems is advancing rapidl
lhft_intern.bib::Ahmed2012c

A Waveguide to Differential Stripline Transition for Planar mm Wave Antenna Measurements - Methfessel, Sebastian Dirk; Schmidt, Lorenz-Peter (Global Symposium on Millimeter Waves, GSMM, 2011)
lhft_intern.bib::Methfessel11

Broadband polarimetric mmWave antennas with differential stripline feed - Thurn, Karsten; Methfessel, Sebastian Dirk; Schmidt, Lorenz-Peter (European Conference on Antennas and Propagation, 2012)
Two approaches for differentially fed, polarimetric antennas with a center frequency of 77.5 GHz are introduced. These are an aperture-coupled patch (ACP) antenna and a monopole antenna with two differentially fed monopole pairs. Easy planar integration with differential MMICs is given through the differential stripline feed. Both antennas are designed for high bandwidth from 70 to 85 GHz for 10 dB return loss and high polarization purity. A stacked conical horn included in both designs results in a high gain of 8.5 dBi and a radiation pattern with one symmetric main beam without significant side lobes, reducing coupling to other elements in a future antenna array. After an introduction, design goals for the antennas are presented. Then, the design procedures for the two concepts are described together with simulation results. For measurement of the antennas, a feed network has been developed and the monopole antenna has been chosen for realization. The paper will be concluded by measurement results that are in good agreement with the simulations.
lhft_intern.bib::Thurn2012

Design and Measurement of a Wideband Aperture-Coupled and Polarization-Agile Stacked-Patch Antenna-Array for Monopulse Radar Applications - Methfessel, Sebastian Dirk; Schmidt, Lorenz-Peter (European Conference on Antennas and Propagation EuCAP, Berlin, March, 2009)
A wideband, circularly-polarized antenna array covering the frequency range 1.7 GHz to 2.5 GHz for telemetric monitoring and monopulse application is presented. Using a subarray design, monopulse functionality can be achieved with an external comparator network. The high bandwidth of 38 % is realized by using the principle of the aperture-coupled stacked-patch microstrip antenna. By integrating a quadrature coupler, the polarization sense can be selected. Sequential rotation technique is used for enhancing polarization purity. The theoretical analysis is based on the finite-difference time-domain (FDTD) method. A stacked-patch antenna element, a 2×2 antenna quadrant and a 4x4 antenna array have been designed, fabricated and measured. The measured return loss of one quadrant is better than 11 dB in the desired bandwidth for both circular polarization senses. Maximum antenna gain ranges between 7 dB and 18 dB for the sum pattern while the null depth of the difference pattern is always better than 30 dB. Theoretical and measured results of S parameters and radiation patterns are presented and discussed.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.design_7

Differential Excitation of a Hybrid Antenna for a 75 GHz Antenna Array Implemented on a Multilayer PC Board - Juenemann, R.; Zielska, A.; Schießl, Andreas; Methfessel, Sebastian Dirk; Schmidt, Lorenz-Peter (43th European Microwave Week, 2013)
If, for practical reasons, there is a need to bend a differential waveguide, the bend has to be compensated to avoid mode conversion into the common mode which can lead to unwanted resonance effects. This paper deals with two possible compensating structures for a 45° bend in a differential waveguide exciting a hybrid antenna. The hybrid antenna in turn is part of a large array used in a security scanner for people screening. Simulations show antenna behavior with and without compensation with respect to matching, mode conversion, gain, and suppression of the cross polarization. © 2013 European Microwave Association.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.differ
Keywords: antenna feed; differential amplifier; horn antenna; microwave imaging; mode conversion

Increasing Measurement Speed in mm-Wave Imaging Systems by Means of Frequency Multiplexing - Koeppel, Tobias; Methfessel, Sebastian Dirk; Schießl, Andreas; Schmidt, Lorenz-Peter (43th European Microwave Week, 2013)
Target movement during illumination causes reliability issues in imaging systems, particularly in applications where time efficiency is needed. A technique is proposed in order to reduce measurement time and as a consequence also motion blur effects. With the use of OFDM waveforms, a decrease in measurement time by a factor of 1.6 is achieved with minimal hardware costs. Measurement time for increasing numbers of carriers is predicted. A hardware realization is investigated with respect to hardware imperfections. Influence of intermodulation distortion and phase noise on dynamic range is discussed. Afterwards, imaging results are presented. © 2013 EMA.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.increa
Keywords: microwave imaging; multistatic radar; signal processing; sparse array

Millimeter-wave imaging concepts: Synthetic Aperture Radar (SAR) and Digital Beam Forming (DBF) - Gumbmann, Frank; Tran, Hue Phat; Cenanovic, Amir; Methfessel, Sebastian Dirk (Frequenz, 2009)
Short range radar imaging systems for various security and non-destructive testing (NDT) applications are mainly based on synthetic aperture radar (SAR) or digital beam forming (DBF) techniques. In this article the development of a real-time SAR and a real-time DBF system is presented. The goal is to achieve a 3D image of a large measurement area with a high lateral and range resolution in order to detect suspicious items or material approach. This can be realized with a SAR system which is based on a new rotating virtual antenna concept. Another approach is a digital beam forming concept consisting of spatially distributed transmitters and receivers. Experimental results on specific test objects are presented to prove the performance of both concepts.
UnivIS-Import:2015-03-09:Pub.2009.tech.IE.LEH.millim
Keywords: Digital beam forming; Millimeter-wave imaging; Synthetic aperture radar

Size-Reduction and Suppression of Cavity-Resonances in Hybrid mm-Wave Antennas for Polarimetric Measurements - Methfessel, Sebastian Dirk; Schmidt, Lorenz-Peter (43th European Microwave Week, 2013)
Size and feed structure are some of the important constraints for using antenna-elements in multi-element two-dimensional arrays, where easy planar integration with transceiver chips is essential. This applies especially when differential signaling and adaptable polarization is required. Based on a balanced-fed patch-excited cavity-backed horn antenna (hybrid antenna), feeding concepts and approaches to reduce size are discussed and evaluated in this paper. The influence of the substrate integrated cavity is analyzed and methods to overcome the restrictions are presented, together with simulated and measured results. The optimized antennas achieve a relative bandwidth of more than 17% for 10 dB return loss, a gain of more than 5 dBi as well as symmetric and homogeneous radiation patterns in amplitude and phase with low cross-polarization. © 2013 European Microwave Association.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.sizere
Keywords: Antenna arrays; Antenna feeds; Aperture coupled antennas; Cavity resonators; Horn antennas; Millimeter wave radar; Radar imaging; Radar polarimetry

Size-reduction and suppression of cavity-resonances in hybrid mm-wave antennas for polarimetric measurements - Methfessel, Sebastian Dirk; Schmidt, Lorenz-Peter (43rd European Microwave Conference, 2014)
Size and feed structure are some of the important constraints for using antenna-elements in multi-element two-dimensional arrays, where easy planar integration and appropriate matching with transceiver chips are essential. This applies especially when differential signaling and adaptable polarization are required. Based on a balanced-fed patch-excited cavity-backed horn antenna (hybrid antenna), feeding concepts, and approaches to reduce size are discussed and evaluated in this paper. The influence of the substrate-integrated cavity is analyzed and methods to overcome the restrictions are presented, together with simulated and measured results. The antenna elements are evaluated with regard to their use in multistatic and polarimetric sparse arrays, which will be briefly introduced. The optimized antennas achieve 10 dB return loss, a gain of more than 5 dBi as well as symmetric and homogeneous radiation patterns in amplitude and phase with low cross-polarization in the desired frequency-band of operation between 70 and 80 GH
lhft_intern.bib::Methfessel2013n

Substrattechnologien für planar integrierte Mikro- und Millimeterwellenschaltungen - Schmidt, Lorenz-Peter; Methfessel, Sebastian Dirk; Schneiderbanger, Dirk; Rehner, Robert; Sterns, Michael; Kilian, Andreas; Nisznansky, Martin (Kooperationsforum Leiterplattentechnologie, Nürnberg, 22.01.2008, S. 95-124, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.substr